2015
DOI: 10.1093/ntr/ntu212
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Medication Use and Cigarette Smoking Cessation: Results From the International Tobacco Control Four Country Survey

Abstract: Women may have more difficulty quitting than men, and SCMs use may help attenuate this difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
125
6
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(136 citation statements)
references
References 41 publications
3
125
6
2
Order By: Relevance
“…Observou-se, neste estudo, maior proporção de cessação abrupta, sendo semelhante ao encontrado em estudos prévios 11,25 . Todavia, resultados de metaanálise mostraram que os tipos de cessação gradual e abrupto apresentavam taxas de cessação comparáveis 26 .…”
Section: Discussionunclassified
“…Observou-se, neste estudo, maior proporção de cessação abrupta, sendo semelhante ao encontrado em estudos prévios 11,25 . Todavia, resultados de metaanálise mostraram que os tipos de cessação gradual e abrupto apresentavam taxas de cessação comparáveis 26 .…”
Section: Discussionunclassified
“…32 We will determine from this study whether it is worthwhile to pursue videoconferencing smoking cessation interventions as an adjunct to telephone counseling interventions such as quitline service for women who tend to have lower success rates with the service. [23][24][25][26][27]32 The study will also test the feasibility of a home-based salivary cotinine test using a NicAlert test strip. The NicAlert test is relatively cost effective compared to CO breath test.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Men are, however, more likely to succeed in quitting, especially when treated with nicotine replacement therapy (NRT). [23][24][25][26][27] Women more frequently report that smoking helps them control stress and negative mood and manage their weight, and are more likely to relapse to smoking after a quit attempt. [27][28][29][30][31] Accordingly, a meta-analysis of smoking cessation studies reported that women in general require more intensive counseling support for quitting than their male counterparts.…”
Section: Kim Et Almentioning
confidence: 99%
“…Evidence suggests that utility of NRTs is particularly important for women. Research from the International Tobacco Control Four Country Surveys showed that women who do not use any medication are less likely to be successful in their cessation attempt and the difference in successful cessation between men and women is removed when medications are used [12].…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that smoking cessation is more difficult to achieve for women than men [12,13]. As many as two-thirds of smokers accessing National Health Service (NHS) stop smoking services are women; however, women are overall less likely to successfully achieve short term cessation through the NHS stop smoking service than men [14].…”
mentioning
confidence: 99%